METODE TREND NON LINEAR UNTUK FORECASTING KOMPOSISI PENDUDUK KABUPATEN TAPANULI TENGAH MENURUT JENIS KELAMIN TAHUN 2006-2016 - Indah Simamora (JURNAL CURERE, 2019)
This study aims to find out how big the prediction of the composition of the population of Central Tapanuli Regency by sex in 2006-2016 by using the Non-Linear Trend: Rank Two Polynomial Method (parabolic trend).Forecasting is a forecast of what will happen in the future. Forecast predicts a value in the future by making a prediction on the composition of the population of Kabupaten Tapanuli Tengah, focusing on gender (male and female) forecasting will be sought separately, after that the total population of the Regency of Tapanuli Tengah will be calculated. Based on these predictions a trend line is produced.This research was conducted by using the Non Linear Trend: Rank Two Polynomial Method (parabolic trend). The trend line is basically a regression line where the independent variable X is a time variable. Both regression lines and trends can be straight lines (linear regression / trend) or not straight (non linear regression/ trend). The parabolic trend line equation is as follows: (t = time).